Pengaruh Return On Asset, Return on Equity dan Non Performing Financing terhadap Pembiayaan Mudharabah Pada PT. Bank Syariah Indoensia - Qurrotul ‘Aini, Eka (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
The purpose of this research is to determine the influence of Return on Asset (ROA), Return on Equity (ROE) and Non-Performing (NPF) on Mudharabah financing at PT. Bank Syariah Indonesia. The research method used is a quantitative method with secondary data obtained from BSI’s quarterly financial reports accessed on the official BSI website. The analysis technique employs multiple linear regression analysis processed using SPSS version 25. The research results indicate that the ROA and ROE variables do not have a partial influence, while NPF shows a positive and significant influence on Mudharabah financing at PT. Bank Syariah Indonesia TBK for the period 2021-2023.